2018
DOI: 10.1039/c8ta08366e
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of dopants in the critical current density for dendrite formation in garnet electrolytes

Abstract: Dopants used to stabilise the cubic phase of LLZO also play a crucial role in the cell's critical current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 39 publications
4
105
0
Order By: Relevance
“…19,28 Subsequent efforts to optimise the ionic conductivity of doped LLZO have seen a number of supervalent (donor) dopants proposed. 29 These include other small cations, such as gallium, that directly substitute lithium; [30][31][32] larger cations, such as tantalum or niobium, that substitute zirconium or lanthanum on the M or M sites; 10 and donor anions, such as fluorine, that substitute oxygen. 33 Donor doping is usually assumed to affect lithium stoichiometry by causing the formation of charge-compenstating lithium vacancies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…19,28 Subsequent efforts to optimise the ionic conductivity of doped LLZO have seen a number of supervalent (donor) dopants proposed. 29 These include other small cations, such as gallium, that directly substitute lithium; [30][31][32] larger cations, such as tantalum or niobium, that substitute zirconium or lanthanum on the M or M sites; 10 and donor anions, such as fluorine, that substitute oxygen. 33 Donor doping is usually assumed to affect lithium stoichiometry by causing the formation of charge-compenstating lithium vacancies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sudo et al revealed a similar phenomenon in Al 2 O 3 contained Li 7 La 3 Zr 2 O 12 .The composition with highest grain boundary conductivity exhibited the longest period before short circuit [104]. Although Pesci et al revealed that Al dopant segregated at the grain boundaries and facilitated the nucleation and propagation of dendrites in Li 6.55 Al 0.15 La 3 Zr 2 O 12 , resulting in a current density of 0.1 mA cm −2 [112]. Their observation still agreed that the high grain boundary conductivity can help to prevent lithium dendrite.…”
mentioning
confidence: 95%
“…The evaporation of lithium during the annealing step can be the reason for this gradient. The incorporation of Al mitigates the segregation of Li towards the surface by forming a lithium aluminate passivation layer at the grain boundaries, [13,14] hence the less graded 7 Li + signal in the Al-doped film. On the surface, the 7 Li + signal is significantly higher, likely due to the presence of lithium hydroxide as a result of exposure to air while loading the samples into the measurement system.…”
Section: Morphology and Elemental Distributionmentioning
confidence: 99%
“…Solid-state fast lithium-ion conductors have been gathering increasing attention in recent years as a feasible alternative to a link between the dopant and the critical current density in the electrolyte. [14] LLZO is generally investigated in the form of pellets, which are fabricated following ceramic sintering processes that require long processing times (above 10 h) and high temperatures (about 1200 °C). This process results in pellets with a diameter of a couple centimeters at maximum and thickness in the millimeter range.…”
Section: Introductionmentioning
confidence: 99%